Asian Financial crises : Origins, implications and solutions. (International Monetary Fund, 2001)
This paper analyzes the origins, implications, and solutions for the Asian financial crisis. From the perspective of a member of the Executive Board of the IMF, as Asian problems were building, the IMF overlooked weaknesses in bank and corporate balance sheets in much of Asia: the IMF was unaware of the extraordinary leverage of Korean companies, which in some cases reached a ratio of 600/1 debt to equity. The IMF did not focus on the weak accounting and disclosure practices of banks and nonbanks or generous rollovers of banks to their key clients.